(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article analyzes Paulo Coelho’s novel “The Alchemist” and its translation into Uzbek by Ozod Sharafiddinov. The article is aimed at studying the artistic expression, philosophical content and spiritual aspects of the translation. The translator’s style in Uzbek and his ability to vividly convey the tone of the text allow the reader to understand the philosophical and artistic content of the novel.